(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The acceleration of energy issues in the economies of different countries is associated with the transportation, extraction, consumption and conversion of energy resources, in particular gas. The Ukrainian gas transportation system is an important part of the country’s export potential, with its favorable geographic location at the crossroads of Europe and Asia. In the article, we will try to analyze whether the gas transportation system for the country is an element of its energy security and one of the decisive components of the national economy. It carries out important functions: the delivery of gas to the Ukrainian market of consumption and transportation through the territory of the country of gas to the countries of Western and Central Europe. At the present stage of development, there are the following main problems of the gas transit system through the Ukrainian GTS: – outdated technology of gas transportation networks; - low level of exploration work for the search of new gas production fields; - a very large dependence on gas imports; – insufficient amount of investments; – in recent years there is a problem of loss of the GTS; – determination of the optimal transit tariff. The status of the transit state of gas gives Ukraine economic and political benefits, as natural gas for many countries of the world is the main product for their fuel and energy complex. The Ukrainian system has proven reliability and transparency. A peculiarity is the fact that the joint operation of trunk pipelines with storage facilities is being carried out. A powerful network of underground gas storage facilities with the largest capacity makes the gas transportation system of Ukraine even more reliable, because in the event of a change in weather it is able to provide the necessary volumes of gas to the consumer countries. The development of Ukraine’s cooperation in the energy sector with other countries is an important driving force of the national economy. The following factors hinder cooperation: – political problems with the main supplier of gas; - uncertainty and low level of communication with foreign-policy systems of international level. However, despite the problems and obstacles, our state is the main transit, and also keeps the total volume of transported gas within its territory within acceptable limits.